2002
DOI: 10.1177/03079459994362
|View full text |Cite
|
Sign up to set email alerts
|

Escalation of Commitment during New Product Development

Abstract: Although periodic review is a prominent feature of new product development (NPD) processes, important questions about how managers make critical continuation/termination decisions in risky NPDprojects remain unanswered. The authors test whether factors unrelated to a new product’s forecasted performance cause managers to continue NPDprojects into subsequent stages of development at rapidly accelerating costs. The results show that managers who initiate a project are less likely to perceive it is failing, are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
180
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(186 citation statements)
references
References 46 publications
3
180
3
Order By: Relevance
“…This result supported those of some other researchers such as [17]; [18] where h igh personal responsibility group reduced escalating commit ment. The result did not supporting other researchers like, [10][11][12] who man ipulated personal responsibility for init ial decision and found that high personal responsibility increased escalation of commit ment.…”
Section: Discussion and Implication Of Fi Ndingscontrasting
confidence: 77%
See 1 more Smart Citation
“…This result supported those of some other researchers such as [17]; [18] where h igh personal responsibility group reduced escalating commit ment. The result did not supporting other researchers like, [10][11][12] who man ipulated personal responsibility for init ial decision and found that high personal responsibility increased escalation of commit ment.…”
Section: Discussion and Implication Of Fi Ndingscontrasting
confidence: 77%
“…Researchers like [10][11][12], manipulated personal responsibi lity for initial decision and found that high personal responsibility increased escalation of commit ment. [13] in a replicat ion of Staw's experiment revealed that there is no escalation of commit ment following negative feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh (1997) finds that preparing a progress report on the project at the time of the setback can reduce escalation of commitment; however, this study does not address preparing a report during the initial phase of capital budgeting. Studies have also found that the use of organization-set hurdle rates is ineffective in reducing escalation of commitment (Cheng et al 2003;Schmidt and Calantone 2002). As a whole, these studies do not make clear what effect the use of capital budgeting techniques will have on escalation of commitment.…”
Section: Literature Review Escalation Of Commitmentmentioning
confidence: 98%
“…Earlier studies in this area include experimental approaches to simulate resource allocation and sharing decisions in a project environment (Bendoly and Swink, 2007) and to understand decision-making processes and learning effects in the project and portfolio management domain (Arlt, 2011). Decision making in product development environments has also been explored experimentally (Schmidt and Calantone, 2002;Spanjol et al, 2011).…”
Section: Research Methods Methodologymentioning
confidence: 99%